Solar CO2 Reduction Using Surface-Immobilized Molecular Catalysts. Issue 1 (2nd January 2016) - Louis, Michael E.; Fenton, Thomas G.; Rondeau, Jarec; Jin, Tong; Li, Gonghu
Abstract : This review article summarizes recent work in developing hybrid photocatalysts by grafting molecular catalysts on solid-state surfaces for solar CO2 reduction. Several surface-immobilized systems are discussed to examine effects of ligand derivatization and surface characteristics on the activities of hybrid photocatalysts. This article also describes the extensive use of spectroscopic techniques in studying hybrid photocatalysts, and briefly introduces research efforts in constructing artificial photosynthetic assemblies based on surface-immobilized CO2 -reduction catalysts. GRAPHICAL ABSTRACT: